2013
DOI: 10.1111/ajt.12404
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils Are Not Required for the Induction and Maintenance of an Alloantibody Response

Abstract: Eosinophil-produced cytokines have been shown to participate in the maintenance of antigen-specific plasma cells (PC) in bone marrow (BM), suggesting that eosinophils are required in the development and/or maintenance of alloantibody responses post-transplant. To test this hypothesis, we sensitized eosinophil-deficient ΔdblGATA1 mice and WT control mice with allogeneic splenocytes or with allogeneic heart grafts and compared the kinetics and titers of serum donor-specific antibodies (DSA), as well as BM and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Therefore, our data indicate that treatment with anti-hCRTh2 in hCRTh2.BAC.Tg mice may only minimally reduce, but not eliminate, plasma cells in the BM. These findings are consistent with data reported by Cravedi et al in eosinophil-deficient dblGATA1 B6 mice where plasma cell numbers showed a minimal to moderate reduction in BM and spleen and no differences in alloantibody titers after immunization (39). Therefore, while reduction in eosinophils may moderately decrease BM plasma cells, it is unlikely to be clinically significant in lowering antibody titers (40).…”
Section: Prolonged Depletion Of Eosinophils With H19a2 Mabs Does Not supporting
confidence: 92%
“…Therefore, our data indicate that treatment with anti-hCRTh2 in hCRTh2.BAC.Tg mice may only minimally reduce, but not eliminate, plasma cells in the BM. These findings are consistent with data reported by Cravedi et al in eosinophil-deficient dblGATA1 B6 mice where plasma cell numbers showed a minimal to moderate reduction in BM and spleen and no differences in alloantibody titers after immunization (39). Therefore, while reduction in eosinophils may moderately decrease BM plasma cells, it is unlikely to be clinically significant in lowering antibody titers (40).…”
Section: Prolonged Depletion Of Eosinophils With H19a2 Mabs Does Not supporting
confidence: 92%
“…134,177,178 Genetic knockout studies, however, have provided mixed results, suggesting that plasma cell-intrinsic signaling by these factors might not all be essential in vivo. [185][186][187][188][189] The integration of these signals with primary plasma cell metabolism, however, has been understudied with a notable recent exception. 178,[180][181][182][183][184] The necessity of some of these cell types and secreted cytokines has been disputed, but a common proposed feature of these populations is their ability to secrete pro-survival cytokines and in turn support plasma cell longevity.…”
Section: Cell Extrinsic Factorsmentioning
confidence: 99%
“…Thus, depletion of eosinophils had moderate success in reducing alloantibody, 52 and inhibiting eosinophil survival by IL-5 blockade has shown some success in experimental models. 53 Such agents are being investigated in clinical trials to treat asthma.…”
Section: Control Of Plasma Cell Function (Menna Clatworthy)mentioning
confidence: 99%